2017
DOI: 10.1186/s12936-017-2109-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic oleanane triterpenoids enhance blood brain barrier integrity and improve survival in experimental cerebral malaria

Abstract: BackgroundCerebral malaria (CM) is a severe complication of Plasmodium falciparum infection associated with high mortality and neurocognitive impairment in survivors. New anti-malarials and host-based adjunctive therapy may improve clinical outcome in CM. Synthetic oleanane triterpenoid (SO) compounds have shown efficacy in the treatment of diseases where inflammation and oxidative stress contribute to pathogenesis.MethodsA derivative of the SO 2-cyano-3,12-dioxooleana-1,9-dien-28-oic acid (CDDO), CDDO-ethyl a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 76 publications
(92 reference statements)
2
16
0
Order By: Relevance
“…Other therapeutic agents that increase Ang1 expression also prevent BBB leak and improve survival in ECM. Mice treated with the ethyl amide of a synthetic oleanane triterpenoid, 2-cyano-3,12-dioxooleana-1,9(11)-dien-28-oic acid (CDDO-EA), had increased Ang1, reduced Ang2 and Ang2:Ang1 ratio, and this was associated with improved BBB integrity ( 208 ). Similarly, treatment of malaria infected mice with the PPAR-γ agonist rosiglitazone in combination with artesunate at the onset of neurological symptoms achieved higher plasma and brain levels of Ang1 and a lower Ang2:Ang1 ratio compared to mice treated with artesunate alone.…”
Section: Therapeutic Interventions Targeting the Ang/tie Axismentioning
confidence: 99%
“…Other therapeutic agents that increase Ang1 expression also prevent BBB leak and improve survival in ECM. Mice treated with the ethyl amide of a synthetic oleanane triterpenoid, 2-cyano-3,12-dioxooleana-1,9(11)-dien-28-oic acid (CDDO-EA), had increased Ang1, reduced Ang2 and Ang2:Ang1 ratio, and this was associated with improved BBB integrity ( 208 ). Similarly, treatment of malaria infected mice with the PPAR-γ agonist rosiglitazone in combination with artesunate at the onset of neurological symptoms achieved higher plasma and brain levels of Ang1 and a lower Ang2:Ang1 ratio compared to mice treated with artesunate alone.…”
Section: Therapeutic Interventions Targeting the Ang/tie Axismentioning
confidence: 99%
“…During CM, dysfunction of the ECs may occur due to adhesion of iRBCs to ECs, the local proinflammatory cytokine response, and increased coagulation of the blood in the microvasculature leading to cerebrovascular constriction ( Figure 2). Synthetic oleanane triterpenoids have been shown to reduce plasma levels of the cytokines IL-10, TNF, and IFN-γ, thereby enhancing the integrity of the BBB during ECM [51]. Recently, Barker et al [52] have implicated micro RNA in the activation of ECs (Figure 4).…”
Section: Factors Governing Endothelial Dysfunction In CMmentioning
confidence: 99%
“…CDDO-EA (Figure 3) is a synthetic oleanolic derivative that has been shown to possess various biochemical activities which include efficacy against cerebral malaria (CM) [129]. The development of severe CM is associated with dysfunction of the Inflammatory events involved in the pathogenesis of cerebral malaria endothelial intercellular junctions in pediatric fatal cerebral malaria [126].…”
Section: Synthetic Oleanolic (So) Pentacyclic Triterpenes Derivativesmentioning
confidence: 99%
“…immune system as shown by plasma levels of TNF-α and IFN-γ [59,130]. A single injection dose of CCDO-EA (200 μmol/kg) lowered circulating levels of TNF-α and IFN-γ which improved mice survival and lowered inflammation [129]. Indeed, studies have indicated that the host's response to malaria is excess production of pro-inflammatory molecules which are thought to be central causes of inflammation in malaria.…”
Section: Synthetic Oleanolic (So) Pentacyclic Triterpenes Derivativesmentioning
confidence: 99%
See 1 more Smart Citation